ANALISIS KINERJA RANTAI PASOK KOPI PADA WARKOP WAW DI KOTA BANDAR LAMPUNG - Arifians, Ridho; Zakaria, Wan Abbas; Rahmalia, Dian (Lampung University, 2025)
This study aims to analyze the condition of coffee supply chain at Warkop Waw and to analyze the performance of coffee supply chain at Warkop Waw that located in Bandar Lampung City. Food Supply Chain Network (FSCN) framework was utilized to analyse the first objective, while the Supply Chain Operation Reference (SCOR) model was used to analyse the second objectives. The data was collected from October 2023 to November 2023. Respondents were included 10 farmers, 10 consumers, and the owner of Warkop Waw. The results of this study show that the supply chain structure consists of suppliers, Warkop Waw, and consumers. The supply chain targets include the nearest collectors, partner companies, coffee shop, consumers, with a focus on developing management and cooperation among supply chain actors, as well as improving the quality and quantity of raw materials. Supply chain management includes effective government support, transaction systems, partner selection, and contracts. Supply chain resources include several aspects: physical technology, human resources, and capital. Risk, distribution patterns, and trust building are the foundation of supply chain business operations. The research results based on the metrics of Perfect Order Fulfillment (POF), Order Fulfillment Cycle Time (OFCT), Flexibility, and Cash-to-Cash Cycle Time (CTCCT) are l fall into the superior category in the supply chain performance assessment, which indicates the highest level of effectiveness on supply chain performance. Key words: coffee shop, agroindustry, performance, supply chain